Antibody-Directed Therapies: Toward a Durable and Tolerable Treatment Platform for CTCL - Khan, Shaheer; Sawas, Ahmed (Frontiers in Oncology, 2019)
Cutaneous T-cell lymphomas (CTCL) are a rare group of heterogenous disorders characterized by cutaneous involvement of monoclonal T-lymphocytes. Although indolent at early stages, CTCL can confer significant morbidity and mortality when advanced. There is an unmet need for tolerable and durable treatments with antibodies recently gaining promise. Here we review approved systemic therapies and discuss select antibodies in development.